Physical activity levels of people over 60 - Tyszko, Weronika (Journal of Education, Health and Sport, 2022)
Introduction: Physical activity at any age brings numerous benefits. In youth, it strengthens and increases a person’s overall physical fitness whereas in old age it improves well-being, inhibits the ageing process and sustains health. With systematic exercise it is possible to maintain physical fitness at a higher level compared to physically inactive people [1]. Physical activity is one of the factors that determines a person’s state of health. Their ontogenesis is also a major element of a healthy lifestyle [2]. The human body was created for movement so, in order to function properly, it needs regular activities and physical exercise [3]. Regular physical activity influences the maintenance of functional fitness, independence and autonomy in performing daily activities in older age. Movement deficiency is a problem at any age, especially in seniors. Maintaining an active lifestyle among the elderly is a major component of successful ageing [4]. Aim of the study: The aim of the study was to assess the physical activity levels in people over 60 years old, and whether there is a correlation between sociodemographic factors, BMI and physical activity levels in the study group. Material and method: The study was conducted remotely in July and August 2020 on people aged 60 and over. The study involved 77 people over 60 years of age: 63 women and 14 men. The research tool was the International Physical Activity Questionnaire (IPAQ). In the study group 69 people were aged 60-70 years and 8 people were aged 71-80 years. Results: People over 60 years of age lead active lifestyles; seniors’ physical activity is sufficient. BMI and socio-demographic factors do not affect the physical activity of older people. Conclusions: The level of physical activity among the elderly covered by the study is sufficient. Sociodemographic factors and BMI do not determine the level of physical activity in the study group.